Towards Testing the UML PSSM Test Suite - Elekes, Márton; Micskei, Zoltán (Anais do Workshop on Validation and Verification of Future Cyber-physical Systems (WAFERS), 2021)
In model-based engineering approaches, models are executable artefacts used for simulation, generation and verification. The Executable UML specifications enriched the well-known UML language with precisely defined semantics. The Precise Semantics of UML State Machines (PSSM) specification defined an operational semantics for state machines. Moreover, the specification contains a detailed test suite that illustrates the semantics and can be used to check the conformance of model execution tools. However, as the test suite itself is a complex engineering effort, it could contain errors. To the best of our knowledge, this is the first paper to test and verify the PSSM test suite. We report on typical errors and issues found by reviewing the specification and executing it in one of the supporting tools. Finally, we collect recommendations for such test suites that could enhance future modelling language specifications.